2015
DOI: 10.1002/ajh.23956
|View full text |Cite
|
Sign up to set email alerts
|

Single‐dose intravenous gammaglobulin can stabilize neutrophil Mac‐1 activation in sickle cell pain crisis

Abstract: Intravenous immunoglobulin (IVIG) decreases neutrophil adhesion to endothelium and red blood cell-neutrophil interactions in sickle cell mice undergoing vaso-occlusion. In this Phase I clinical trial of sickle cell anemia (SCA) patients admitted with pain crisis, we evaluated the status of adhesion molecules on neutrophils in control and IVIG-treated subjects pre- and post-infusion up to 800 mg/kg, the same dose used in murine studies. Mac-1 function significantly decreased from baseline in the low-dose IVIG (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 28 publications
0
32
0
1
Order By: Relevance
“…162,164 Furthermore, a clinical trial using intravenous immunoglobulin infusions to block Fc γ RIII receptor mediation of secondary activity on neutrophils in children with SCD in crisis is in process (ClinicalTrials.gov identifier: NCT01757418). 165 A functional in-vitro adhesion test, such as the SCD biochip, could be a useful tool for measuring patients’ response to treatment. Moreover, the SCD biochip could be adopted as an in-vitro model in which to test therapeutics that target cellular adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…162,164 Furthermore, a clinical trial using intravenous immunoglobulin infusions to block Fc γ RIII receptor mediation of secondary activity on neutrophils in children with SCD in crisis is in process (ClinicalTrials.gov identifier: NCT01757418). 165 A functional in-vitro adhesion test, such as the SCD biochip, could be a useful tool for measuring patients’ response to treatment. Moreover, the SCD biochip could be adopted as an in-vitro model in which to test therapeutics that target cellular adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a pan-selectin inhibitor, rivipansel (GMI-1070), has been shown in phase II studies to reduce the time to resolution of systemic vaso-occlusive pain crisis and opioid administration in SCD patients (39). In a separate phase I study, intravenous immunoglobulin (IVIG) was shown to inhibit Mac-1 activation on neutrophils in SCD patient blood (40). Recently, an oral P-selectin inhibitor was also shown to improve microvascular blood flow in SCD patients (41).…”
Section: Discussionmentioning
confidence: 99%
“…112 IVIG administration in SCD patients in a phase 1 study demonstrates no significant adverse events with doses up to 800 mg/kg, indicating safety and tolerability in acute VOC. 113 Because lower doses show better biomarker and clinical efficacy profiles, the 400 mg/kg dose is selected for further study in an ongoing phase 2 trial (#NCT01757418). Numerous preclinical and early phase clinical studies have demonstrated the benefit of targeting P-selectin.…”
Section: Targeting Neutrophilsmentioning
confidence: 99%